JOB DESCRIPTION (JOBDESC) TOUR LEADER DALAM PENANGANAN PERJALANAN WISATA DI TRAVEL AGENT MYTRIP INDONESIA ENDRIFI - Putri, Elsa; Yulia, Nur Arini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2026)
This study discusses the job description of Tour Leaders in managing travel activities at Mytrip Indonesia Endrifi Batam Travel Agent. The background of this research is based on tourist complaints regarding Tour Leader services, such as delayed information, lack of friendliness, and insufficient responsiveness to tourists’ needs. The purpose of this study is to identify and analyze the job description of Tour Leaders at each stage of the travel process, including pre-tour (before the trip), on-tour (during the trip), and post-tour (after the trip). This study uses a descriptive qualitative method with data collection techniques including observation, interviews, and documentation involving managers, staff, Tour Leaders, and tourists. The results indicate that the job description of Tour Leaders plays a crucial role in ensuring smooth travel experiences. At the pre-tour stage, Tour Leaders prepare travel documents and necessary arrangements; during the on-tour stage, they coordinate the itinerary, maintain comfort, and resolve issues that arise; and at the post-tour stage, they prepare reports and conduct evaluations. The conclusion emphasizes that the job description of Tour Leaders greatly affects tourist satisfaction and the company’s image, highlighting the need for improved communication skills, excellent service, and conflict management. Keywords: Tour Leader, Job Description, Travel Management, Tourist Satisfaction, Mytrip Indonesia.